2020
DOI: 10.1016/j.neurobiolaging.2020.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effect of APOE and polygenic component on Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a devastating neurodegenerative condition with significant genetic heritability. Several genes have been implicated in the onset of AD with the apolipoprotein E ( APOE ) gene being the strongest single genetic risk loci. Evidence suggests that the effect of APOE alters with age during disease progression. Here, we aim to investigate the impact of APOE and other variants outside the APOE regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 38 publications
(66 reference statements)
8
30
1
Order By: Relevance
“…Recently another study, investigating subjects that do not overlap with our study and using different parameters, reported a greater effect of APOE in younger participants (Bellou et al, 2020). Our stratified interaction analysis indicating a larger effect of PRS non-APOE in younger APOE4 carriers leads us to a novel conclusion about APOE -independent genetic risk and provides a logical explanation for their observation: among all APOE4 cases, those with a younger onset carry the largest PRS non-APOE .…”
Section: Discussionsupporting
confidence: 53%
“…Recently another study, investigating subjects that do not overlap with our study and using different parameters, reported a greater effect of APOE in younger participants (Bellou et al, 2020). Our stratified interaction analysis indicating a larger effect of PRS non-APOE in younger APOE4 carriers leads us to a novel conclusion about APOE -independent genetic risk and provides a logical explanation for their observation: among all APOE4 cases, those with a younger onset carry the largest PRS non-APOE .…”
Section: Discussionsupporting
confidence: 53%
“…Future studies should further investigate this avenue of brain-behaviour relationships in older age. They should consider inclusion of the wider range of genetic 40 and environmental 41 variables, and thus probably reduce the misclassifications shown in the present study, as well as other predictive models and methods within modern machine learning frameworks 36 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The oligogenic risk score (ORS.no.APOE) (based on SNPs with pT ≤ 10 − 5 ) also decreases in cases with age but is on average higher than in controls, with the highest being in ORS.no.APOE for ε44 cases as reported in 8 . Contrary to ORS.no.APOE, the mean of PRS.no.APOE (blue line) is higher in older cases and lower in older controls 16 . Thus, because of the changing allelic frequencies of APOE genotypes over age, it is clear that the APOE genotype by itself and the ORS.no.APOE become much less accurate predictors in older cases, while the reverse is seen with the PRS.no.APOE score.…”
Section: Optimal P-value Thresholdmentioning
confidence: 97%
“…It has been shown that the PRS contribution to AD risk differs with age and APOE-ε4 allele status. For example, the effect of PRS (pT ≤ 0.5) is more pronounced in older people 16 , and the effect of oligogenic risk scores constructed using SNPs with an association pT ≤ 1e-5 is greater in ε4 homozygotes 8 . Based upon these observations, we hypothesised that unaccounted age-related genetic differences (in particular the APOE-ε4 agedependent frequency) lead to the disagreement about the optimal p-value threshold and the consequent debate about oligogenic (ORS) vs polygenic (PRS) disease models.…”
Section: Introductionmentioning
confidence: 99%